STRATEGI PEMASARAN BERDASARKAN KONSEP PRODUCT LIFE CYCLE (PLC) PADA WEDDING ORGANIZER (WO) SALMA WEDDING CONCEPT DI KOTA BANDUNG - Purwanti, Yanti; Diana, Reja Agung (ITB AAS Indonesia Surakarta, 2024)
Salma Wedding Concept is a company engaged inwedding service. Established in December 2020, but Salma Wedding Concept just confirmed focus and have office in january 2021. Salma Wedding Concept also hastagline separate ie â€œConcept Your Wedding Dream With Usâ€ where is salma Wedding Concept this will help the aspirantsclient to make your dream wedding come true with attitude, responsibility, sincerity, and millenials idea. The purpose of this research was conducted: to find out the general description of Salma Wedding Concept, to find out the application analysis Product Life Cycle (PLC) on Salma Wedding Concept, and to find out the right marketing strategy to develop Salma Wedding Concept in the city of Bandung based on the concept PLC. The research method used is descriptive with a qualitative approach. Primary data collection techniques are carried out by observation, in-depth interviews (in depth interview) and documentation. As well as secondary data collection techniques obtained from sources of books and journals. Based on the results of this study, it shows Salma Wedding Concept are in the maturity stage (maturity) according to Philip Kotler's theory, namely this period the sales growth tends to be slower and even from October 2022 to February 2023 the revenue decreases. This is marked by the emergence of new competitors that have sprung up and many competitors who have lowered their prices below standard so that there are many devotees, with that the interest of the public is starting to diminish in Salma.Wedding Concept this and cause the earned income to decrease.